The assessment of the toxicity of nanocomplexes containing gadolinium orthovanadate nanoparticles and cholesterol - Goltsev, A.N.; Bondarovych, M.; Babenko, N.; Gaevska, Yu.; Ostankova, L.; Ostankov, M.; Volkova, N.; Klochkov, V. (Cell and Organ Transplantology. 2021; 9(1):44-52., 2021)
Nanocomplexes (NCs) synthesized at the Institute for Scintillation Materials of the National Academy of Sciences of Ukraine, consisting of nanoparticles (NPs) of gadolinium orthovanadate and cholesterol, are promising compounds that can be used as probes and fluorescent labels for tumor cells or experimental oncopathology treatment. However, the biosafety of such substances remains unclear. The PURPOSE of the study was to evaluate the acute toxic effect of nanocomplexes on the healthy mice. MATERIALS AND METHODS. Nanocomplexes containing nanoparticles of GdYVO4:Eu3+ and cholesterol in 5 % glucose solution were administered to BALB/c mice once intraperitoneally in volumes of 0.1 mL, 0.5 mL, 1 mL, 2 mL, which corresponds to 5.9-6, 5 mg, 29.5-32.5 mg, 59.1-65.0 mg, 118.2-130.0 mg/kg body weight. Control animals were injected with the same volumes of 5 % glucose solution. On the 14th day, the morphological characteristics of organs, the number of CD34+CD38– cells among bone marrow total nucleated cells, the activity of gammaglutamyl transferase (GGT) and glucose-6-phosphate dehydrogenase (G6PD) in liver homogenates were determined. RESULTS. With the administration of NPs at a dose of less than 118.2 mg/kg body weight, no fatalities and symptoms of intoxication were showed, but there was a dose-dependent increase in the content of GGT in the liver of experimental animals. The use of NPs at a dose of 118.2-130.0 mg/kg body weight resulted in the death of 50 % of the animals on the 3rd day. In this group, on the 14th day, there were neoplasms in the spleen of one of the surviving animals, a decrease in the number of bone marrow total nucleated cell on the background of increased hematopoietic stem cells with CD34+CD38– phenotype, necrotic and dystrophic changes in the liver, and decreased activity of the G6PD enzyme. CONCLUSIONS. The potential median lethal dose of gadolinium orthovanadate nanoparticles and cholesterol in nanocomplexes was determined, which was 118.2-130.0 mg/kg animal body weight, which allows to classify them as low-toxic substances.
Goltsev A., Bondarovych M., Babenko N., Gaevska Yu., Ostankova L., Ostankov M., Volkova N., Klochkov V. The assessment of the toxicity of nanocomplexes containing gadolinium orthovanadate nanoparticles and cholesterol. Cell and Organ Transplantology. 2021; 9(1):44-52.
Keywords: nanoparticles; nanocomplexes; gadolinium orthovanadate; median lethal dose